Short and tweet a uses & gratifications study of Twitter use for local news - San Jose, Denise Valerie Arcilla
"This study examines the use of social media website Twitter by local news agencies for news dissemination as well as its reception by the general Filipino audience. The researcher first conducted focus interviews on the Twitter moderators of ABS-CBN News (@ABSCBNNews), ANC (@ANCALERTS), Inquirer.net (@inquirerdotnet) and Philstar.com (@PhilstarNews). The results revealed that the aforementioned news agencies decided to make Twitter accounts for their respective news companies to be able to propagate information to a broader audience, increase readership and/or viewership and to verify and disseminate news in real time. The researcher then surveyed 100 random Filipino Twitter users on their use of Twitter as a news source. Majority of them (96%) found Twitter an effective source of news with only a few (4%) regarding it as neither effective now ineffective. The top reasons for them preferring Twitter as a news source is that news is delivered fast, the media is accessible and is capable of easily directing them to multimedia content."